Direct current triggering enhanced anaerobic treatment of acetyl pyrimidine-containing wastewater in up-flow anaerobic sludge blanket coupled with bioelectrocatalytic system. (September 2019) - Wang, Dexin; Li, Yangyang; Zhuang, Haifeng; Yi, Xuesong; Yang, Fei; Han, Hongjun
Abstract: In this study, the novel up-flow anaerobic sludge blanket coupled with bioelectrocatalytic system (UASB-BEC) was developed with the attempt to enhance treatment of acetyl pyrimidine-containing wastewater. The results revealed that higher current applied had a positive effect on acetyl pyrimidine (AP) degradation but a negative impact could be followed by the overhigh current (>1.26 A m −3 ). Removal efficiencies of AP and total organic carbon (TOC) were as high as 96.3 ± 2.6% and 92.9 ± 3.2% while methane production reached up to 0.70 ± 0.03 NL-CH4 L −1 -reactor d −1 at applied current of 1.26 A m −3, which were significantly higher those in control system. Moreover, high-throughput 16S rRNA gene pyrosequencing further indicated that Desulfovibrio and Methanimicrococcus species were specially enriched in suspended sludge and cathodic biofilm with current involvement. It could be reasonably speculated that enrichment of Desulfovibrio and Methanimicrococcus species could promote biotransformation of AP and final H2 -depended methylotrophic methanogenesis. This study could shed light on better understanding of AP transformation in bioelectrocatalytic system and provide a valuable reference to practical application of anaerobic AP-containing wastewater treatment. Graphical abstract: Image 1 Highlights: Novel UASB-BEC was proposed for enhanced treatment of AP-containing wastewater. Electric stimulation could contribute to forming more aggregated biomass. Desulfovibrio -enriched electroactive biofilm was participated in conversion of AP. H2 -depended methylotrophic methanogenesis was main methanogenic pathway in UASB-BEC.